ROLE OF AGNI KARMA AND SNEHAPANA IN MANAGEMENT OF PAIN IN CERVICAL SPONDYLOSIS: A CASE STUDY - Charde, *Vaibhav Anandrao; Amit, Dr.; Nair, Parvathy G; Deep, V C (International Journal of Ayurveda and Pharma Research, 2017)
Introduction: Cervical spondylosis (Greevasthamba) is a degenerative condition with pain in cervical region as a major symptom. In modern science condition is usually treated with analgesic, corticosteroids, surgical decompression, traction etc. which not contribute much promising results. But in Ayurveda several methods like Snehana, Upanaha, Agnikarma, Raktamokshana and Panchakarma etc. are specified in management of pain. Case presentation: A male patient aged 42 years admitted CARIN-MSD, IPD with pain in the neck region since 2 months, which was also radiating to the right upper limb along with numbness up to the tip of fingers. Cervical active range of motions were painful during flexion, extension and lateral rotation. Spurling test and lhermittes sign were positive. Along with the support of X- ray and MRI investigations the patient was diagnosed with cervical spondylosis due to chronic postural strain. Management and Outcome:Patient was treated with Agnikarma and Snehapana, the pain score over visual analogue scale and NPQ percentage before treatment was Nine and 87.5 % respectively while after intervention it was reduced to Two and 33.33 % within seven days. Conclusion: In acute painful stage of cervical spondylosis Agnikarma and Snehapana can play a major role in management of pain.